Advances in the development and optimization strategies of the hemostatic biomaterials - Guo, Yayuan; Cheng, Nanqiong; Sun, Hongxiao; Hou, Jianing; Zhang, Yuchen; Wang, Du; Zhang, Wei; Chen, Zhuoyue (Frontiers in Bioengineering and Biotechnology, 2023)
Since most injuries are accompanied by the risk of bleeding, timely hemostasis is necessary to relieve pain and reduce mortality. In addition to traditional methods of hemostasis, such as zeolite and gauze, a variety of excellent hemostatic agents have emerged on the market in recent years, including inorganic, protein-based, polysaccharide-based and synthetic materials. The most prominent ones are biodegradable collagen sponges (Helistat®, USA), gelatin sponges (Ethicon®, SURGIFOAM®, USA), chitosan (AllaQuixTM, ChitoSAMTM, USA), cellulose (Tabotamp®, SURGICEL®, USA), and the newly researched Extracellular matrix gum, etc. While these hemostatic materials have excellent hemostatic properties, they also have advantages and disadvantages. In this review, the performance characteristics, hemostatic effects, applications and hemostatic mechanisms of various biomaterials are presented. Then, several strategies to improve hemostasis are shown, including modification of single materials, blending of multiple materials, design of self-assembled peptides and their fusion materials. Finally, the future research direction is to explore the coagulation mechanism of hemostatic biomaterials to develop more novel hemostatic biomaterials.